Mobile Phones, Household Welfare and Women's Empowerment : Evidence from Rural Off-grid Regions of Bangladesh - Hossain, Monzur; Samad, Hussain (Taylor and Francis, 2021)
Using household survey data from off-grid regions of rural Bangladesh, this study attempts to assess the impacts of mobile phone use on household welfare and women’s empowerment. Using two propensity score-based weighted regressions (IPW and AIPW), this study finds that mobile phone use increases household income (3 to 10 percent) from different sources, such as small businesses and remittances; improves women’s empowerment; and facilitates consumption smoothing during periods of shocks. Thus, favorable policies on investment in mobile telephone technologies, tariffs on talk time and internet usage, and mobile innovations, such as mobile financial services could reduce communication bottlenecks and digital divide in rural lagging regions that will help achieve a balanced regional development. Simultaneously, policies to avoid adverse impact of mobile phone usage should also be in place.